Comparison of stent and indomethacin suppository efficacy in the prevention of acute pancreatitis after ERCP - Icacan, Gamze; Onalan, Erhan; Yucesoy, Mehmet (Mattioli 1885, 2021)
Objective: We aimed to compare stent and indomethacin suppository efficacy in the prevention of acute pancreatitis after ERCP. Materials and Methods: 76 high-risk patients undergoing ERCP were included in the study. The patients were divided into three groups as indomethacin group, stent group and control group. Indomethacin group (n = 32) received 100 mg rectal indomethacin immediately after ERCP. A 5F pancreatic stent was applied to the stent group (n = 16) during ERCP. No prophylaxis was given to the control group (n = 28). Results: There was no difference between the groups in terms of age and gender. ERCP pancreatitis was seen in 9.2% (7/76) of the patients. The incidence of ERCP-induced pancreatitis (PEP) was 3.1% (1/32) in the indomethacin group and 21.4% (6/28) in the control group. PEP was not seen in the stent group (0/16). The incidence of PEP was significantly lower in the indomethacin group than in the control group (p = 0.043). However, no significant difference was found between the stent and control groups, stent and indomethacin groups in terms of PEP frequency (p = 0.072, p: 0.90 respectively). Conclusion: According to the results of our study, rectal indomethacin administration decreased the frequency of PEP in high-risk patients. However, there was no significant difference in PEP prophylaxis between the stent and indomethacin groups. © Mattioli 1885.
Keywords: Endoscopic retrograde cholangiopancretiography; ındomethacin; Non-steroidal antiinflammatory drug; Post-ERCP pancreatitis